Perinevic dermatosis neglecta: clinical and dermoscopic description - Vincenzo Piccolo; Teresa Russo; Lilian Mathias Delorenze; Giuseppe Argenziano (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Perinevic dermatosis neglecta is an underestimated skin condition usually affecting children and adolescents, characterized by the appearance of dirt-like brownish pigmentation around a preexisting nevus and often a matter of concern for parents. We describe the clinical and dermoscopic findings in a case of perinaevic dermatosis neglecta and discuss the possible etiology of this phenomenon.